Quantification of the emesis scale (puqe-24) through giving ginger wedding to 1st trimester pregnant women - Sibero, Jitasari Tarigan; Fitria, Aida; Priyah, Wiknish Banu (Institute Of Computer Science (IOCS), 2024)
Nausea, vomiting or morning sickness is the most common symptom experienced in early pregnancy due to an imbalance in the hormones estrogen and progesterone. To determine the quantification of the emesis scale (PUQE-24) before being given Wedang Ginger at the Fina Sembing Clinic in Medan in 2023. To determine the quantification of the emesis scale (PUQE-24) after being given Wedang Ginger. To analyze and determine the effect of giving Wedang Ginger to reduce emesis gravidarum in Pregnant Women in the 1st Trimester. Using a quasi-experimental design with a one group pretest posttest design that has treatment. The sampling technique was purposive sampling, namely 10 respondents with all respondents given treatment, while the sample was taken from the entire population. The data analysis used in this research is univariate analysis and bivariate analysis with the Wilcoxon test. The research showed that pregnant women in the first trimester who experienced emesis gravidarum before and after giving ginger tea had a p value = 0.003 < 0.05, indicating that Ho would be rejected and Ha would be accepted. Conclusion: there is an effect of giving ginger tea to reduce emesis gravidarum in pregnant women in the first trimester at the Fina Sembiring Clinic, Medan. It is hoped that health workers can apply ginger tea to pregnant women in the first trimester who experience nausea and vomiting as an additional therapy to accompany conventional medicine for pregnant women.